AN ANALYSIS OF EFFECTIVE TEACHERS’ QUESTIONING STRATEGIES IN EFL CLASSROOM INTERACTION: A STUDY AT SMA NEGERI 1 MAKASSAR - Hadrawati Hasanuddin; Ayu Hapsari Hasanuddin; Ayu Sanjani (Universitas Islam Negeri Alauddin Makassar, 2021)
Questioning Strategy is a crucial element in establishing communication between teachers and students in classroom interaction. This study was aimed at analyzing the effective teachers’ questioning strategies in EFL Classroom interaction. It also investigated the reasons effective teachers utilized the strategies. This research applied a case study and employed a discourse analysis approach. Participants in the study were two effective English teachers of SMA Negeri 1 Makassar which were chosen based on the result of the students’ perception questionnaire. The data were collected through observation, audio-video recording, and interviews. The findings revealed that rephrasing, simplification, repetition, decomposition, probing, translating, and blank-filling were applied by both effective teachers as their questioning strategies. Probing was the dominant strategy that effective teachers used in classroom interaction. It also showed that the teacher utilized the strategies to avoid failure in eliciting verbal responses, expand their answer, develop their critical thinking, release the embarrassment and build up confidence. Furthermore, by utilizing these questioning strategies particularly probing, the teacher could expand students’ responses and make the students more attentive and engaged in the teaching and learning process.